Hubungan Asupan Zat Gizi Makro, Pemberian MP-ASI, dan Riwayat ASI Eksklusif dengan Kejadian Stunting pada Anak Usia 6-24 Bulan di Suku Tengger - Anisah Firdaus Rahmawati; Lailatul Muniroh; Fina Zahrotun Ni'mah (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Stunting is one of the nutritional major problems for toddlers globally. Based on the 2022 Indonesian Nutrition Status Survey (SSGI), the stunting rate in East Java Province is still relatively high, namely 19.2%. This study aims to analyze the relationship between intake of macronutrients, Complementary Feeding Practice and Exclusive Breastfeeding History with Childhood Stunting Aged 6-24 Months in the Tengger Ethnic. This research method uses a cross sectional research design with a sample size of 42 respondents selected by simple random sampling. Data collection was carried out through questionnaires and interviews, measuring body length, and 2x24 hour food recall. Data were analyzed using Fisher's Exact test. The results of this study indicate that as many as 23.8% of children experience stunting. Based on the test results it is known that there is no relationship between the level of energy, protein, fat, and carbohydrates adequacy, as well as exclusive breastfeeding history, age first given complementary feeding practice, frequency of complementary feeding practice, number of complementary feeding practice, texture of complementary feeding practice (p>0,05) with stunting. The conclusion of this study is that the majority of the intake of macronutrients energy, protein, fat, and carbohydrates in children aged 6-24 months in the Tengger Tribe is mostly classified as deficient, the exclusive breastfeeding history is still low, and the complementary feeding practice related to the first age and the amount given is largely inappropriate.